Bad Boys and Mean Girls: Callous-Unemotional Traits, Management of Disruptive Behavior in School, the Teacher-Student Relationship and Academic Motivation - Allen, Jennifer L.; Bird, Elisabeth; Chhoa, Celine Y. (Frontiers in Education, 2018)
Callous-unemotional (CU) traits comprise a temperament dimension characterised by low empathy, interpersonal callousness, restricted affect and a lack of concern for performance. CU traits are the hallmark feature of psychopathy in youth and are associated with more varied, severe and stable antisocial behaviour. However, little is known about the presentation, impact and correlates of CU traits in schools. We conducted a mixed methods study investigating the relationships between CU traits, student disruptive behaviour, responses to classroom management strategies, teacher-student relationship quality and academic motivation. Participants comprised 437 children aged 11 to 14 years (M = 12.5 years, 51% female) and 12 teachers recruited from a state school in England. Teacher participants consisted of 8 women and 4 men aged 23 to 51 (M = 35.27 years, SD = 10.43). Children completed the Inventory of Callous-Unemotional Traits (ICU; Frick, 2004). Teachers then completed an interview and questionnaires for a randomly selected subsample of students who i) scored in the top 25% on student report of CU traits (n = 24), and ii) scored below the median (n = 23). Thematic analysis of teacher interviews revealed that high CU children display more frequent, severe antisocial behaviour in school. Teachers reported that high CU students were resistant to teacher discipline strategies, often showing intense displays of anger in response to their attempts to set limits. High CU students appeared to be less responsive to social rewards (e.g., praise). Encouragingly, some teachers reported a good relationship with a child identified as high in CU traits, despite recognizing that this student’s behaviour made it difficult for other teachers to maintain a harmonious classroom environment. Teachers attributed the poor academic performance of children high in CU traits to a lack of motivation, reporting the need for intense monitoring and feedback to ensure that these students completed schoolwork. Findings suggest that risk pathways for poor school outcomes may differ for antisocial children high and low in CU traits, and emphasize the need to modify existing school-based interventions to promote academic engagement and prosocial behaviour in this high-risk subgroup of antisocial children.